EXPRESSING VOICE IN A FOREIGN LANGUAGE: MULTIWRITING HAIKU PEDAGOGY IN THE EFL CONTEXT - Iida, Atsushi (TEFLIN Journal, 2017)
One of the crucial perspectives in the teaching of second language (L2) writing is to develop voice (Iida, 2010; Paltridge et al., 2009). While scholars have discussed the significance of teaching voice from theoretical viewpoints, there is scant reporting on how to teach the concept and how to train L2 writers to express their own thoughts in the target language in the composition classroom. The aim of this article is to discuss how L2 writers can develop their voice through poetry writing in the L2 composition classroom. After describing the concept of voice and the feature of multiwriting, this article will explore the potential of multiwriting haiku pedagogy as a way to develop and express voice in the EFL freshman college writing classroom. It will also present a step-by-step approach for multiwriting haiku in the EFL classroom and then illustrate how Japanese EFL writers express voice and articulate self in the poetic text with the pedagogical guidelines.